Konsep Kesejahteraan Sosial Menurut Masyarakat Melayu Di Batubara - Chairun Nisa; Yakobus Ndoda (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to explore the concept of social welfare according to the Malay community in Batu Bara, North Sumatra, in the context of the fifth principle of Pancasila values: "Social Justice for All Indonesian People." Welfare here is defined as a state where the basic needs of individuals and society are met fairly and equally, including aspects of economics, health, education and psychological well-being. This research uses a qualitative approach with ethnographic methods, involving participant observation and in-depth interviews with community leaders, families and individuals in Batubara. The research results show that the concept of social welfare in the Malay community in Batubara is strongly influenced by Islamic cultural and religious values, which are in line with the principles of social justice in Pancasila. Social solidarity, mutual cooperation and zakat are the three main pillars that support social welfare in this community. Social solidarity is realized through the practice of helping each other in various social activities, while mutual cooperation is reflected in cooperation in infrastructure development and traditional events. Zakat, as a religious obligation, plays a significant role in the redistribution of wealth and alleviation of poverty.